2011
DOI: 10.1088/0957-0233/22/7/075203
|View full text |Cite
|
Sign up to set email alerts
|

Wall shear stress sensor based on the optical resonances of dielectric microspheres

Abstract: We report an optical wall shear stress sensor based on the whispering gallery mode (WGM) shifts of dielectric micro-resonators. The optical resonators are spheres with a typical diameter of several hundred microns and they serve as the sensing element. The wall shear force acting on a movable plate is transmitted mechanically to the microsphere. As a result of the applied force, the shape of the resonator is perturbed leading to a shift of the optical resonance (WGM). The one-dimensional wall shear stress is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…Therefore, in our experiments the strain range is limited so that WGMs shift is less than one FSR corresponding to 0.33% (3250 μɛ) axial elongation of the polymer wire. The spectral shift of the WGM resonant wavelength due to axial strain can be described as a combined effect of changing diameter and the changing refractive index of the resonator [8][9][10][11][12][13][14][15]23]:…”
Section: Sensing Principle Operation and Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in our experiments the strain range is limited so that WGMs shift is less than one FSR corresponding to 0.33% (3250 μɛ) axial elongation of the polymer wire. The spectral shift of the WGM resonant wavelength due to axial strain can be described as a combined effect of changing diameter and the changing refractive index of the resonator [8][9][10][11][12][13][14][15]23]:…”
Section: Sensing Principle Operation and Fabricationmentioning
confidence: 99%
“…There are many reports concerning WGM strain sensing using spherical [8][9][10][11][12][13][14] as well as bubble [15,16] MRs based on silica and polymer materials. Typically, an evanescent light coupling technique is used to excite the WGMs in such MRs.…”
Section: Introductionmentioning
confidence: 99%
“…Tangentially coupling the light to the cavity is one of the easiest methods to let the light start to interrogate through the total internal reflection of the cavity [12,[16][17][18], as shown in Figure 1a. Recently, MDR micro-cavities have been used in applications including spectroscopy [19,20], micro-cavity laser technology [21], optical communications (switching [22], filtering [23], and multiplexing [24]), and sensor technologies [3,4,8,12,15,17,[25][26][27][28][29][30][31][32][33]. In this paper, the electric field imposes a force on the dielectric microsphere (commonly referred to as the electrostriction effect) leading to the deformation of the sphere.…”
Section: Measurement Approachmentioning
confidence: 99%
“…The second assumption is that there is a measurable change in the refractive index brought about by the different mechanical stress and strain components within the resonator material. Taken together, the fractional change in the wavelength of the WGMs is [21][22][23][24][25][30][31][32] Δλ λ ΔD D Δn n ;…”
Section: A Effect Of Strain On the Wgm Resonance Wavelengthmentioning
confidence: 99%
“…Measurement sensitivity can be improved by using dielectric materials with smaller elastic modulus, such as polymers. For example, Ioppolo et al [21][22][23][24] have demonstrated that solid, as well as hollow polymethyl-methacrylate (PMMA), microspheres have a higher strain sensitivity compared to those made of silica.…”
Section: Introductionmentioning
confidence: 99%